Swaziland : Country Integrated Fiduciary Assessment - World Bank (Washington, DC, 2013)
The objective of this assessment was to identify key Public Financial Management (PFM) risks and mitigating actions (reforms) that the Government should plan and implement, in consultation with development partners. The agreed PFM reform programme will endeavour to mitigate key risks in achieving aggregate fiscal discipline, efficient resource allocation, and efficient and effective delivery of public services (development purpose) and accountability. In addition, it will attempt to establish a level of fiduciary assurance for donors that funds will be applied for their intended purpose with economy, efficiency and effectiveness (fiduciary purpose). The remainder of this report contains background information on PFM in Swaziland (section two), an explanation of the scores for individual performance indicators (section three), key risks and recommended mitigating actions/reforms (section four) and a summary description of the government's reform programme (section five). Annexes include - the summary of the performance indicator scores (annex A); a comparison of the results from the 2007 assessment with 2009 (annex B); the calculation of deviations by budget head for the period 2006-2008 (annex C); the list of sources used for each indicator (annex D); the list of participants met during the CIFA assessment meetings (annex E); the new PFM bill (annex F) and a document reference list (annex G).